Atomic-resolution monitoring of protein maturation in live human cells by NMR. - Banci, L; Barbieri, L; Bertini, I; Luchinat, E; Secci, E; Zhao, Y; Aricescu, A (2013)
We use NMR directly in live human cells to describe the complete post-translational maturation process of human superoxide dismutase 1 (SOD1). We follow, at atomic resolution, zinc binding, homodimer formation and copper uptake, and discover that copper chaperone for SOD1 oxidizes the SOD1 intrasubunit disulfide bond through both copper-dependent and copper-independent mechanisms. Our approach represents a new strategy for structural investigation of endogenously expressed proteins in a physiological (cellular) environment.